PENERAPAN METODE MONTECARLO UNTUK GERAK PENGONTROLAN ROBOT BERBASIS RANDOM WALKS - Muhammad Ridwan Effendi (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
The development of science and technology encourages the development of robots. Robots are widely used in various fields of human life to facilitate human life. Robot making has developed both in terms of methods and algorithms used in robots. The use of the montecarlo method and the random walks algorithm are widely implemented in robot designs at present.     The basic concept of the Montecarlo method in solving differential equations is the probability of a random walk. Based on the approach in the random step process, the Montecarlo method is known for two types of approach that are quite popular, namely the fixed random walk type and the floating random walk type. For this research, the researcher intends to apply the monte carlo method to control the motion of a randon walk based robot. In this research method, the research stages will be described including needs analysis, application of the monte carlo method, making applications to control robots using Arduino.The results of this research, testing using the Montecarlo method, show that the response of the robot is not too slow, the new robot reacts not too far beyond the existing speed change limit. From the above tests, it can be analyzed that the application of the Montecarlo method is more effective and efficient in measuring motion in the robot. Keywords : Montecarlo Method, Robot Control, Randon Walks